Developing stakeholder participation to address lack of safe water as a community health concern in a rural province in South Africa. Issue 1 (1st January 2021) - Hove, Jennifer; D'Ambruoso, Lucia; Twine, Rhian; Mabetha, Denny; van der Merwe, Maria; Mtungwa, Ishmael; Khoza, Sonto; Kahn, Kathleen; Witter, Sophie
ABSTRACT: Background: Despite legislative and policy commitments to participatory water governance in South Africa, and some remarkable achievements, there has been limited progress to improve the water infrastructure servicing in marginalized rural communities. Around five million South Africans still do not have access to safe water. Objective: This paper seeks to understand and advance processes to engage multisectoral stakeholders to respond to lack of safe water as a community-nominated health priority in rural South Africa. Method: We engaged representatives from Mpumalanga Department of Health (MDoH), rural communities, other government departments and non-governmental organisations (NGOs) to cooperatively generate, interpret and act on evidence addressing community-nominated priorities. A series of participatory workshops were conducted where stakeholders worked together as co-researchers to develop shared accounts of the problem, and recommendations to address it. Consensus on the problem, mapping existing planning and policy landscapes, and initiating constructive dialogue was facilitated through group discussions in a collective learning process. Results: Community stakeholders nominated lack of safe water as a local priority public health issue and generated evidence on causes and contributors, and health and social impacts. Together with government and NGO stakeholders, this evidence was corroborated. Stakeholders developed a local action plan through consensus and feasibility appraisal. Actions committed to behavioural change and reorganization of existing services, were relevant to the needs of the local community and were developed with consideration of current policies and strategies. A positive, collective reflection was made on the process. The greatest gain reported was the development of dialogue in 'safe spaces' through which mutual understanding, insights into the functioning of other sectors and learning by doing were achieved. Conclusion: Our process reflected willingness and commitment among stakeholders to work together collectively addressing local water challenges. Location in an established public health observatory helped to create neutral, mediated spaces for participation.